Circle Wars: Reshaping the Typical Autism Essay - Melanie Yergeau (Disability Studies Quarterly, 2009)
This piece investigates “typical autism essays” and their rhetorical commonplaces, their largely neurotypical discourse conventions. In the field of rhetoric and composition, circular metaphors in discourse community theory resemble popular representations of autism as a low-functioning/high-functioning binary. Each field-specific conversation attempts to define groups of people (student writers, autistics) as though there are hard and fast boundaries to one’s identity. I posit that typical autism essays obscure issues of power as well as their neurotypically-defined genre conventions, effectively denying autistic self-advocates a place in the conversations that concern them. Keywords: Autism; autistics; circles; cognitivism; discourse communities; essays; genre theory; neurodiversity; neurotypicality; rhetoric and composition; spectrum
Keywords: Autism; autistics; circles; cognitivism; discourse communities; essays; genre theory; neurodiversity; neurotypicality; rhetoric and composition; spectrum